Understanding the Factors Influencing the Leisure Tourism Behavior of Visually Impaired Travelers: An Empirical Study in China - Qiao, Guanghui; Zhang, Junmiao; Pabel, Anja; Chen, Nan (Frontiers in Psychology, 2021)
This study looks at the real-world problems which vision impaired individuals face when they travel. More specifically, this study aims to explore the main factors influencing the leisure tourism behaviours of visually impaired individuals. Based on in-depth semi-structured interviews with 26 visually impaired respondents, this study identifies six main factors impacting on the leisure tourism behaviours of visually impaired individuals including: tourism products and services, personal psychological factors, social support, community support, personal socio-economic factors, and barrier-free environments. Findings show that visually impaired travellers have strong requirements for auditory, tactile, and physical participation. Support factors such as escorts, tour organizers specifically targeting their experiential offerings at the visually impaired, and an accessible environment are important considerations for visually impaired travellers. Findings also show that visually impaired individuals participate in leisure tourism to enhance their own abilities, relieve pressures on their families, break stereotypes associated with the visually impaired, and promote the need for greater tourism development specifically targeting visually impaired travellers. This study also proposes a theoretical model outlining the factors influencing leisure tourism of visually impaired people.